The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4049/jimmunol.180.1.261
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacute Rejection by Anti-Gal IgG1, IgG2a, and IgG2b Is Dependent on Complement and Fc-γ Receptors

Abstract: We have previously reported that anti-Gal-α1,3Gal (Gal) IgG3 mAbs mediate a classical complement-dependent hyperacute rejection (HAR), while anti-Gal IgG1 mAbs mediate HAR that is dependent on complement, the Fc-γ receptors FcγRII/III (CD32/CD16), and NK cells. IgG2a and IgG2b subclasses can activate complement and have FcγR binding properties in vitro. Whether these IgG subclasses can mediate HAR in vivo and the mechanisms by which they would do so are not known. In this study, we isolated spontaneous IgG swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Moreover, in both fast and slow progressors, the anti-Amot antibodies were mainly IgG2a and IgG2b (Fig. S4), the most active subclasses in both complement- [25] and antibody-dependent cellular cytotoxicity [26].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in both fast and slow progressors, the anti-Amot antibodies were mainly IgG2a and IgG2b (Fig. S4), the most active subclasses in both complement- [25] and antibody-dependent cellular cytotoxicity [26].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…IgG2b was reported to mediate hyperacute rejection in rat cardiac xenografts in a complement dependent manner (13). We tested the binding of IgG2b to tumor cells by flow cytometry in the following experiments.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report (30) showed that IgG2b can mediate hyperacute rejection in rat cardiac xenografts in a complement-dependent manner. We proceeded by examining if the immune sera collected in Fig.…”
Section: Cancer Researchmentioning
confidence: 99%